Nachos for dinner : surprising sheet pan meals the whole family will love - Whalen, Dan (Workman Publishing, 2021)
"It's like a dream come true! First, because you now have permission to eat a plate of nachos as a real meal, and second, because here are dozens and dozens of recipes and ideas to elevate this beloved snack into a legitimate and nourishing sheet pan dinner. Plus dessert. Written by the irrepressible Dan Whalen, Nachos for Dinner combines the mad-genius spirit of his previous books, 'Smores and Tots!, with the practical brilliance of Sheet Pan Suppers. First Whalen breaks down the nacho's intrinsic appeal to its three essential components-a crispy base, a melty sauce, and a flavorful topper. And then he gives you the three flavor profiles-a lot of umami, a little heat, and something sour or pickled. From there the world is your nacho plate. Of course there's the chips-and-cheese classic, but then the nachos veer decidedly into dinner, with favorites from every part of the meal from French Onion Nachos, Buffalo Chicken Nachos, and Cobb Salad Nachos to Fish Taco Nachos, Banh Mi Nachos, and Shrimp and Grits Nachos. And there are plenty of not-chos (that is, nachos that use other ingredients for the chips)-like Lasagnachos, Scallion Pancake Nachos, and Pretzel and Brat'chos. Even Apple Pie Nachos for dessert"--